2016
DOI: 10.1063/1.4943076
|View full text |Cite
|
Sign up to set email alerts
|

Research Update: Spin transfer torques in permalloy on monolayer MoS2

Abstract: We observe current induced spin transfer torque resonance in permalloy (Py) grown on monolayer MoS2. By passing rf current through the Py/MoS2 bilayer, field-like and damping-like torques are induced which excite the ferromagnetic resonance of Py. The signals are detected via a homodyne voltage from anisotropic magnetoresistance of Py. In comparison to other bilayer systems with strong spin-orbit torques, the monolayer MoS2 cannot provide bulk spin Hall effects and thus indicates the purely interfacial nature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
76
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(85 citation statements)
references
References 33 publications
7
76
1
Order By: Relevance
“…Shao et al (2016) showed that the FL torque in 1 nm CoFeB deposited on monolayer MoS 2 and WSe 2 is of the order of 0.1-0.14 mT/10 7 Acm −2 , independently of temperature, and is consistent with iSGE-induced spin accumulation, whereas the DL torque is negligibly small. Sizable DL SOTs, on the other hand, have been reported for NiFe deposited on MoS 2 (Zhang et al, 2016c) and on the semi-metal WTe 2 (MacNeill et al, 2017). The latter case is of particular interest as the surface crystal structure of WTe 2 has only one mirror plane and no two-fold rotational invariance about the c-axis, which allows for a DL torque that is directed out-of-plane when the current is applied along a low-symmetry axis of the surface.…”
Section: Fm/semiconductor Layersmentioning
confidence: 99%
See 1 more Smart Citation
“…Shao et al (2016) showed that the FL torque in 1 nm CoFeB deposited on monolayer MoS 2 and WSe 2 is of the order of 0.1-0.14 mT/10 7 Acm −2 , independently of temperature, and is consistent with iSGE-induced spin accumulation, whereas the DL torque is negligibly small. Sizable DL SOTs, on the other hand, have been reported for NiFe deposited on MoS 2 (Zhang et al, 2016c) and on the semi-metal WTe 2 (MacNeill et al, 2017). The latter case is of particular interest as the surface crystal structure of WTe 2 has only one mirror plane and no two-fold rotational invariance about the c-axis, which allows for a DL torque that is directed out-of-plane when the current is applied along a low-symmetry axis of the surface.…”
Section: Fm/semiconductor Layersmentioning
confidence: 99%
“…In the framework of the Rashba model, it can be shown that λ REE = α R τ s / , where α R is the Rashba coupling strength and τ s the relaxation time of the spin/momentum polarization at the Rashba-split Fermi surface (Gambardella and Miron, 2011;Rojas-Sánchez et al, 2013). Typical values of λ REE range from 0.1-0.3 nm in NiFe/Ag/Bi layers (Rojas-Sánchez et al, 2013;Zhang et al, 2015b) to -0.6 nm in NiFe/Cu/Bi 2 O 3 (Karube et al, 2016). Because of the much slower spin relaxation in insulating systems, λ REE can reach extremely large values in heterostructures including a 2D electron gas confined at a polar oxide interface such as NiFe/LaAlO 3 /SrTiO 3 , in which λ REE can be tuned between -6 and 2 nm by electric gating (Lesne et al, 2016;Song et al, 2017).…”
Section: Surface Alloys and Two-dimensional Gasesmentioning
confidence: 99%
“…As we have seen in the previous sections of this feature article, magnetization control can be achieved via spin‐orbit coupling. Strong current‐induced spin‐orbit torques induced at a monolayer MoS 2 ‐Permalloy interface have been reported recently . To effectively capitalize on this opportunity, it would be advantageous to impose magnetic control over the otherwise intrinsically nonmagnetic and insulating TMDs.…”
Section: Transition Metal Dichalcogenides (Tmds)mentioning
confidence: 99%
“…Angular dependent studies are of particular interest because measurement at one in-plane angle may not reveal all the physics within a given system. To wit, the presence of new phenomenological torques acting on the system can be overlooked, 39,40 and hysteresis effects which may be impacting interface transparency 41,42 could be missed. An example of a system that has recently benefited from a complete in-plane study is the magnetic insulator system YIG and the well understood spin Hall metal Pt configured into a ST-FMR experiment.…”
Section: Antiferromagnets: Materials Of Interestmentioning
confidence: 99%